Electroplating method for battery connector terminal
Through surface pretreatment and nanometal coating deposition, combined with the use of functional conductive coating and graphene-based composite coating, the problems of insufficient surface pretreatment effect of battery connector terminals and insufficient corrosion resistance of single-layer metal coating are solved, achieving efficient conductive performance and long-term stability.
Patent Information
- Application Number
- CN202510038971.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, the surface pretreatment effect of battery connector terminals is insufficient, resulting in poor coating bonding power; the single-layer metal coating has microcracks and pores, and insufficient corrosion resistance; the conductive coating has not optimized the electron flow path, and the conductive performance fluctuates greatly; the lack of subsequent curing treatment leads to insufficient long-term stability and durability of the coating.
Technical solutions for surface pretreatment combined with the deposition of the underlying nanometal coating include alkaline cleaning, pickling activation and drying treatment to form a dense metal protective film; functional conductive coating and graphene-based composite coating are deposited on the underlying coating to optimize the electron flow path and enhance corrosion resistance; ultraviolet curing and heat treatment of the coated terminals to form a stable coating structure.
It improves the corrosion resistance and conductivity of the battery connector terminals, enhances the long-term stability and durability of the coating, extends service life, and maintains power transmission stability in complex environments.
Smart Images

Figure CN119819561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery connector manufacturing, and in particular to a battery connector terminal electroplating method. Background Art
[0002] Battery connector terminals are key power transmission components in electronic devices, and their performance directly affects the power transmission efficiency and service life of the equipment. As electronic devices develop towards high power density, lightweight and complex working environments, especially in extreme environments such as high temperature, high humidity or salt spray, higher requirements are placed on the conductivity, corrosion resistance and long-term stability of battery connector terminals.
[0003] In the prior art, the main method to improve the performance of battery connector terminals is to optimize them through electroplating processes, including surface cleaning, single-layer metal plating and composite coating processes. Common surface cleaning methods include chemical cleaning, mechanical polishing, etc. These methods provide a certain degree of clean surface for subsequent coating electroplating. In terms of coating electroplating, traditional processes mostly use single-layer metal plating, such as copper or nickel plating, to improve the conductivity and corrosion resistance of the terminals.
[0004] However, the existing technology still has shortcomings in many key aspects. On the one hand, the effect of surface pretreatment is limited, mechanical grinding is easy to damage the substrate, and a single chemical cleaning method is difficult to completely remove the oxide layer, resulting in insufficient coating adhesion. On the other hand, due to the presence of microcracks and pores, the single-layer metal coating cannot provide long-term corrosion protection in high humidity and high salt spray environments. In addition, the conductive coating is not optimized for the electron flow path, the conductive performance fluctuates greatly, and the contact resistance is high. Finally, the existing technology lacks subsequent curing treatment of the coating, resulting in insufficient stability and durability of the coating in long-term use. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for electroplating battery connector terminals, which solves the problems in the prior art such as insufficient surface pretreatment effect resulting in poor coating adhesion, microcracks and pores in the single-layer metal coating resulting in insufficient corrosion resistance, large fluctuations in conductivity due to failure to optimize the electron flow path in the conductive coating, and insufficient long-term stability and durability of the coating due to lack of subsequent curing treatment.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A battery connector terminal electroplating method, comprising the following steps: Pre-treat the battery connector terminal surface to remove impurities and oxides; Use nano-metal electroplating solution to electroplate the bottom coating of the battery connector terminal to form a dense metal protective film; depositing a functional conductive coating on the base coating to optimize electron flow paths; Applying graphene-based composite coatings on functional conductive coatings to enhance conductivity and corrosion resistance; The coated battery connector terminal is subsequently cured to obtain a battery connector terminal with high corrosion resistance and excellent conductivity. The method can improve the power transmission stability of the terminal and extend its service life.
[0007] Preferably, the pretreatment step comprises: Immerse the battery connector terminals in an alkaline cleaning solution with a mass ratio of 2% to 5%, and perform ultrasonic cleaning at 35°C to 50°C; The cleaned battery connector terminals are immersed in a 3% to 7% hydrochloric acid solution for pickling activation for 2 to 5 minutes; after rinsing with deionized water, the battery connector terminals are dried at 75 to 90° C. for 3 to 7 minutes.
[0008] Preferably, the nanometal electroplating solution is a copper-nickel alloy electroplating solution, the concentration of copper ions is 30-40 g / L, the concentration of nickel ions is 10-20 g / L, and 2-5 g / L of potassium sodium tartrate as a complexing agent and 4-6 g / L of sodium citrate as a dispersant are added during the electroplating process.
[0009] Preferably, the bottom coating is electroplated in a pulse electroplating mode with a pulse period of 8 to 12 ms, a duty cycle of 40% to 60%, and a current density of 1.5 to 3 A / dm 2 The electroplating temperature is 40-50°C, the electroplating time is 25-35 minutes, and ultrasonic assistance with a frequency of 35-45kHz and a power of 250-350W is applied during the electroplating process.
[0010] Preferably, the functional conductive coating is composed of a nickel-based material doped with silver nanoparticles, the average size of the silver nanoparticles is 5 to 10 nm, the mass ratio accounts for 0.5% to 1.5% of the total weight of the functional coating, and the nickel ion concentration is 15 to 25 g / L.
[0011] Preferably, the deposition of the functional conductive coating adopts a direct current plating mode with a current density of 0.8 to 1.5 A / dm 2 The electroplating temperature is 45-55°C, the electroplating time is 12-20 minutes, and a magnetic stirrer is used to stir the electroplating solution at a speed of 80-120 rpm during the electroplating process.
[0012] Preferably, the main components of the graphene-based composite material coating are graphene and polyetheretherketone, the mass ratio of the graphene is 2% to 4%, the mass ratio of the polyetheretherketone is 95% to 97%, and the graphene is uniformly distributed in the polyetheretherketone by a high-speed shear dispersion method.
[0013] Preferably, the graphene-based composite material is coated by spin coating, with a coating thickness of 10 to 20 μm, and after coating, it is cured using ultraviolet light with a wavelength of 350 to 380 nm, and the curing time is 1.5 to 3 minutes.
[0014] Preferably, the bonding force between the functional conductive coating and the graphene-based composite material coating is enhanced by spraying a silane coupling agent, and the concentration of the silane coupling agent solution is 0.1% to 0.5%.
[0015] Preferably, the surface resistance change rate of the obtained battery connector terminal is less than 5% in the temperature range of -40 to 80°C, and its corrosion resistance is shown in a salt spray test as a corrosion resistance time of 1000 to 1500 hours in a 5% sodium chloride solution.
[0016] The present invention provides a battery connector terminal electroplating method, which has the following beneficial effects: 1. The present invention adopts a technical solution of combining surface pretreatment with deposition of an underlying nano-metal coating. By sequentially performing alkaline cleaning, acid activation and drying treatments on the surface of the battery connector terminal, impurities and oxide layers are removed to provide a clean and active bonding interface for subsequent coatings. At the same time, the high density and uniformity of the nano-scale copper-nickel alloy coating are utilized to effectively improve the corrosion resistance of the terminal. Compared with the technical solution of using a single chemical cleaning or ordinary metal electroplating in the prior art, the problem of poor coating bonding and the easy appearance of microcracks or voids in the coating is solved.
[0017] 2. The present invention adopts a technical solution of combining functional conductive coating with graphene-based composite material coating. By depositing a nickel-based conductive coating doped with silver nanoparticles on the underlying coating, the electron flow path is optimized and the contact resistance is reduced. At the same time, the graphene-based composite material is coated on the surface of the conductive coating. The high conductivity and excellent chemical stability of graphene are used to further improve the overall conductivity and corrosion resistance. Compared with the technical solution in the prior art that only relies on a single-layer metal coating to provide conductivity, this solves the problems of large fluctuations in conductivity, high surface resistance of the coating, and poor durability.
[0018] 3. The present invention adopts a technical solution of curing and heat treatment of a multi-layer coating structure. By combining UV curing with heat treatment, a stable bonding interface is formed between the coatings, and the density of the coating and the ability to release residual stress are improved, thereby further enhancing the mechanical strength and power transmission stability of the coating in a complex environment. Compared with the technical solution of the prior art that lacks multi-layer coating interface treatment or subsequent curing steps, the problem of easy peeling of the coating, insufficient environmental adaptability and short service life is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 , an embodiment of the present invention provides a battery connector terminal electroplating method, comprising the following steps: S1. Pre-treating the surface of the battery connector terminal to remove impurities and oxides; Generally, oil, oxides and other impurities are often attached to the surface of the battery connector terminal. If these pollutants are not removed in time, it may cause the metal ions in the electroplating solution to be difficult to evenly adhere to the terminal surface, resulting in problems such as loose bonding of the electroplating layer and uneven distribution of the coating. In some embodiments, the battery connector terminal is first degreased and cleaned. The purpose of degreasing and cleaning is to remove oil or organic pollution that may exist on the terminal surface. As an option, degreasing and cleaning can use an alkaline cleaning solution, preferably a 2% to 5% NaOH solution as the cleaning solution. Specifically, the battery connector terminal is immersed in the above-mentioned NaOH solution and placed in an ultrasonic cleaning equipment for treatment. The cleaning temperature is generally controlled at 35°C to 50°C, the ultrasonic frequency is preferably 35 to 45kHz, and the cleaning time is controlled at 8 to 12 minutes. Under this condition, the cavitation effect generated by the ultrasonic wave can effectively destroy the molecular structure of the oil and improve the cleaning effect. After cleaning, the terminal surface needs to be rinsed immediately with deionized water. Generally, the number of rinses is 3 to 5 times, and the time of each rinse is controlled within 20 to 40 seconds to ensure that the NaOH cleaning solution is completely removed, so as to avoid the generation of residual alkaline substances in the subsequent steps that affect the quality of the electroplating layer; after completing the degreasing cleaning, the battery connector terminals need to be pickled and activated. The purpose of pickling and activation is to remove the oxide layer on the surface of the terminal and expose the active sites on the metal surface through the acidic environment. As an implementation method, pickling activation can be treated with a hydrochloric acid solution, preferably a 3% to 7% hydrochloric acid solution. Specifically, the cleaned terminal is immersed in a hydrochloric acid solution for a period of 2 to 5 minutes. During the pickling process, hydrochloric acid can react with metal oxides to form water-soluble compounds, as shown in the following reaction: MeO+2HCl→MeCl2+H2O, wherein Me represents a metal ion (such as copper or nickel). Through the above chemical reaction, the oxide layer on the metal surface can be quickly removed to expose the active metal surface. After the pickling is completed, the terminal surface is rinsed multiple times with deionized water, generally 4 to 6 times, and each rinse time is 20 to 40 seconds, to ensure that the acid residue is completely removed, thereby avoiding its impact on the subsequent electroplating solution; In a possible implementation, in order to ensure that the terminal surface will not be oxidized or contaminated after pickling, the terminal surface needs to be dried. Specifically, the rinsed terminal can be placed in a hot air drying oven. The drying temperature is preferably 75°C to 90°C, and the drying time is generally 3 to 7 minutes. Hot air drying can quickly remove residual moisture on the surface and prevent the terminal surface from being re-oxidized. In some embodiments, in order to further optimize the cleaning effect of the terminal surface, a corrosion inhibitor, such as citric acid or benzotriazole, can also be added during the pickling activation process. The role of the corrosion inhibitor is to prevent the acid from causing excessive corrosion to the terminal metal substrate, while ensuring that the oxide layer can be evenly removed. The amount of corrosion inhibitor added is generally 0.05% to 0.1%; In other embodiments, in order to improve the activation effect, a mixed acid may be used for pickling, such as a mixed acid solution of hydrochloric acid and nitric acid. Specifically, hydrochloric acid and nitric acid may be mixed in a volume ratio of 2:1 to prepare an activation solution. The activation time is preferably 2 to 4 minutes. The mixed acid has a stronger oxidizing ability and is suitable for processing terminals with thick or difficult-to-remove oxide layers. Step S1 pre-treats the surface of the battery connector terminal to remove impurities and oxides. As a pre-step for electroplating, its purpose is to provide a clean and active surface condition for the subsequent deposition of the nano-metal coating. This step is closely connected with the electroplating step in the entire technical solution, and directly determines the adhesion performance and coating uniformity of the subsequent electroplating layer, thereby ensuring that the final prepared battery connector terminal has excellent corrosion resistance and conductivity.
[0022] S2. Electroplating the bottom coating of the battery connector terminal with a nano-metal electroplating solution to form a dense metal protective film; The specific implementation of the bottom electroplating process is as follows: In some embodiments, a nano-metal electroplating solution is first prepared. As an option, the nano-metal electroplating solution adopts a copper-nickel alloy system, which has the advantage that copper provides excellent electrical conductivity, while nickel can significantly enhance the corrosion resistance of the coating. Specifically, the main components of the electroplating solution include: Copper sulfate (CuSO4·5H2O): concentration is 30-40 g / L, used to provide copper ions; Nickel sulfate (NiSO4·6H2O): concentration is 10-20 g / L, used to provide nickel ions; Potassium sodium tartrate (KNaC4H4O6): concentration is 2-5 g / L, used as a complexing agent to prevent metal ions from precipitating in the solution; Sodium citrate (C6H5Na3O7): concentration of 4-6 g / L, used as a dispersant to inhibit the agglomeration of nanoparticles; Deionized water: used to dilute the above solution to 1L; In one possible implementation, to ensure uniform composition of the electroplating solution, the above formula needs to be placed in a high-speed stirrer and stirred at a speed of 800 to 1200 rpm for 15 to 25 minutes. To avoid oxidation of the solution, nitrogen protection can be introduced during the stirring process; In general, the temperature and pH value of the plating solution have an important influence on the deposition effect of metal particles. Specifically, in this embodiment, the temperature of the plating solution is controlled within the range of 40°C to 50°C and is adjusted by a constant temperature control device. At the same time, the pH value needs to be controlled between 3.5 and 4.5, which can be adjusted by adding a small amount of dilute sulfuric acid or ammonia water; In some embodiments, the battery connector terminal is used as the cathode during the electroplating process, and the anode material is an insoluble titanium anode to reduce the generation of impurity ions in the electrolyte. To enhance the electroplating effect, a pulse electroplating mode is used and controlled by the following process parameters: Current density: 1.5~3A / dm 2 ; Pulse period: 8~12ms, duty cycle 40%~60%; Plating time: 25-35 minutes; The advantage of pulse plating is that it can achieve uniform layered deposition of nanoparticles through periodic current regulation and effectively reduce the hydrogen bubbles generated during the deposition process, thereby improving the density and surface finish of the coating; Specifically, in a possible implementation, in order to further improve the uniformity and density of the coating, ultrasonic assistance can be applied during the electroplating process. The cavitation effect of ultrasonic waves can reduce the diffusion resistance of metal particles in the electrolyte and promote the deposition of particles on the terminal surface. As an option, the frequency of the ultrasonic wave is set to 35-45kHz, and the power range is 250-350W; In order to ensure the bonding strength between the metal coating and the substrate, the coating needs to be post-processed after electroplating. Specifically, the electroplated terminals need to be rinsed with deionized water several times to remove the electrolyte residue on the surface. Subsequently, the terminals are placed in a heat treatment environment at 180°C for 1 hour. Through heat treatment, the grain boundary structure between the nanoparticles can be further optimized, thereby significantly improving the mechanical strength and adhesion of the coating; In some other embodiments, the ratio of copper-nickel alloy can be adjusted to optimize the corrosion resistance of the coating. For example, by increasing the concentration of nickel ions (15-20 g / L), the corrosion resistance of the coating can be further enhanced, but the conductivity may be affected to a certain extent. In order to balance the conductivity and corrosion resistance, the ratio of copper-nickel alloy can be set to Cu:Ni=70:30 (mass ratio); In the process of nano-metal coating formation, the deposition rate is an important parameter that affects the thickness and uniformity of the coating. In general, the deposition rate can be calculated by Faraday's formula: v: deposition rate (μm / min); I: current density (A / cm 2); M: molar mass of the metal (Cu is 63.55 g / mol, Ni is 58.69 g / mol); n: valence of the metal ion (Cu is 2, Ni is 2); F: Faraday constant (96485 C / mol); ρ: density of the metal (Cu is 8.96 g / cm 3 , Ni is 8.90g / cm 3 ); By adjusting the current density and the concentration of copper-nickel ions, the coating thickness can be controlled within the range of 50 to 100 nm, and the coating surface is smooth and free of microcracks. The bottom nano-metal coating formed in this step can improve the corrosion resistance of the battery connector terminal and provide a uniform and stable bonding interface for the subsequent functional conductive coating. This step is closely connected with the surface pretreatment process of step S1. By depositing a layer of high-density and uniform nano-metal coating on the pretreated active metal surface, a stable bonding basis is further provided for the subsequent conductive coating and composite coating. At the same time, the coating can effectively enhance the corrosion resistance of the terminal, reduce the surface defect rate, and improve the overall electrical performance. In this step, nano-copper-nickel alloy is used as the core component of the electroplating solution, and pulse electroplating and ultrasonic assistance are used to ensure the uniform deposition and density of metal particles.
[0023] S3, depositing a functional conductive coating on the base coating to optimize the electron flow path; In this embodiment, the deposition of the functional conductive coating specifically includes the following: In some embodiments, a plating solution for a functional conductive coating is first prepared. As an option, the core component of the plating solution includes a composite system of silver nanoparticles and a nickel-based ion solution. Specifically, silver nanoparticles are an important component for optimizing the electron flow path of the coating due to their high conductivity and excellent dispersibility, while nickel ions provide the mechanical strength and antioxidant properties of the coating. The formula of the plating solution is as follows: Nickel sulfate (NiSO4·6H2O): concentration is 15-25 g / L, used to provide nickel ions; Silver nanoparticles (average particle size 5-10 nm): mass ratio 0.5%-1.5%, evenly distributed in the electroplating solution; Sodium citrate (C6H5Na3O7): concentration of 1.5-3 g / L, used as a dispersant to prevent the agglomeration of silver nanoparticles; Deionized water: make up to 1L for solvent dilution.
[0024] In one possible implementation, in order to improve the uniformity of the electroplating solution, a high-speed shear disperser is used to disperse the silver nanoparticles. Specifically, the above solution is placed in a disperser and dispersed at a speed of 4500-5500 rpm for 30 minutes to ensure that the silver particles are evenly distributed. To further enhance stability, a small amount of surfactant (such as polyethylene glycol, with a concentration of 0.1%-0.2%) can be added during the dispersion process to reduce the sedimentation of the silver particles under static conditions.
[0025] In general, the deposition of functional conductive coatings is carried out by direct current electroplating. Specifically, the plated component (i.e., the battery connector terminal) is used as the cathode, and the insoluble titanium anode is used as the anode. An electric field is formed in the electrolyte, causing silver nanoparticles and nickel ions to be deposited on the cathode surface. The electroplating process parameters are set as follows: Current density: 0.8~1.5A / dm 2 ; Electroplating temperature: 45℃~55℃; Electroplating time: 12 to 20 minutes; Stirring speed: 80-120 rpm, using a magnetic stirrer to ensure uniform flow of the plating solution; In some embodiments, in order to reduce the generation and adhesion of hydrogen during the deposition process, a liquid circulation system can be designed in the electroplating tank to further enhance the diffusion rate of metal ions. In this design, the electroplating solution is circulated at a flow rate of 5 to 10 L per minute through a liquid circulation pump, which effectively improves the deposition efficiency and coating quality; In one possible implementation, to ensure the conductivity and uniformity of the functional coating, the coating thickness needs to be strictly controlled within the range of 10 to 20 nm. The thickness is mainly controlled by the precise matching of current density and electroplating time. The specific calculation can refer to Faraday's formula: Q=I·t Where: Q: current (Coulomb); I: current intensity (A); t: electroplating time (s); m: deposited mass (g); M: molar mass of the plated metal (58.69 g / mol for nickel); n: number of electrons in the metal ion (2 for nickel and 1 for silver); F: Faraday constant (96485 C / mol). By adjusting the current density I and the electroplating time t, the metal deposition amount m can be precisely controlled to achieve a coating of the desired thickness. Specifically, the functional conductive coating in this step mainly relies on silver nanoparticles to form a conductive network. The silver particles are combined through van der Waals forces and metal bonds to form a continuous high-conductivity path. At the same time, nickel metal serves as a matrix to enhance the durability and resistance to environmental interference of the coating. During the electroplating process, the Brownian motion and electrostatic interaction of the silver particles form a stable deposition on the surface of the substrate. This deposition structure effectively reduces the impedance of electron migration.
[0026] In some other embodiments, in order to further optimize the conductive properties of the coating, a small amount of conductive additives, such as amino acid derivatives or organic amine complexes (concentration of 0.01% to 0.1%), can be added to the electroplating solution. These additives can adjust the surface charge distribution of the silver particles and prevent excessive agglomeration of the particles, thereby improving the uniformity of the deposited layer.
[0027] After the electroplating is completed, the coating needs to be cleaned and dried. As an option, the plated parts can be rinsed with deionized water for 3 to 5 times, each rinsing time is 30 seconds to remove the residual electroplating solution components, and then the cleaned plated parts are placed in a hot air drying oven at 75℃ to 90℃ for 5 to 10 minutes; The surface resistance of the functional conductive coating formed by the above method can be controlled within 0.006-0.008Ω / cm 2 range and has excellent power transmission performance. Combined with the coating structure and material properties, this step provides a stable foundation for the adhesion of the graphene-based composite coating while ensuring the conductive stability of the overall coating; This step is closely connected with step S2. On the basis of the high density and corrosion resistance of the underlying coating, the conductivity and power transmission stability of the terminal are further improved. By introducing doping materials (such as silver nanoparticles) into the conductive coating, a uniform functional conductive layer is formed, thereby optimizing the electron migration path, while reducing resistance fluctuations and improving the overall conductivity and environmental adaptability of the coating. The process technology of this step is centered on electroplating deposition, combined with material particle size optimization and surface deposition condition control to ensure the uniformity of the functional coating and the stability of the conductive network.
[0028] S4, coating a graphene-based composite material coating on the functional conductive coating to enhance the conductivity and corrosion resistance; in this embodiment, the coating step of the graphene-based composite material coating specifically includes the following: In some embodiments, a coating liquid of a graphene-based composite material coating is first prepared. As an option, the coating liquid is made of polyetheretherketone (PEEK) as a matrix material, supplemented with graphene powder and a dispersant. Graphene powder, with its unique two-dimensional structure, provides excellent electrical conductivity and can form a stable conductive network in the coating. Specifically, the formula of the coating liquid includes: Graphene powder: 2% to 4% by mass, used to provide high conductivity of the coating; Polyetheretherketone (PEEK): The mass ratio is 95% to 97%, which serves as a matrix material to provide mechanical strength and chemical resistance to the coating; Polyethylene glycol (PEG): The mass ratio is 0.3% to 0.7%, which serves as a dispersant to ensure that the graphene powder is evenly distributed in the matrix.
[0029] In general, graphene powder needs to be pretreated to improve its dispersibility in the matrix. In some embodiments, the graphene powder can be dispersed by a high-speed shear disperser. Specifically, the above formula is placed in a disperser and dispersed at a speed of 4500 to 5500 rpm for 25 to 35 minutes until the graphene particles are evenly distributed in the matrix. In addition, in order to avoid agglomeration of graphene particles, a surfactant (such as polyoxyethylene-polyoxypropylene copolymer, with a concentration of 0.05% to 0.1%) can be added during the dispersion process.
[0030] In one possible implementation, in order to improve the stability of the coating liquid, the graphene powder can be further dispersed with the assistance of ultrasound. Specifically, the dispersed coating liquid is placed in an ultrasonic oscillator and treated at a frequency of 35 to 45 kHz for 10 to 15 minutes, thereby further reducing the tendency of graphene particles to agglomerate.
[0031] During the coating process, the functional conductive coating first needs to be surface treated to ensure the adhesion performance of the graphene-based composite material coating. Generally, the functional conductive layer can be cleaned with deionized water and then placed in a hot air drying oven at 75°C to 90°C for 5 to 10 minutes to remove surface residues.
[0032] In this embodiment, the graphene-based composite coating is coated by spin coating. Specifically, the prepared graphene-based coating liquid is evenly dripped on the surface of the functional conductive coating, and the spin coating is performed at a rotation speed of 1500 to 2500 rpm for 30 to 60 seconds to form a uniform coating thickness. As an option, the thickness of the coating is controlled at 10 to 20 μm, and precise control can be achieved by adjusting the amount of spin coating liquid and the rotation speed.
[0033] In some embodiments, in order to enhance the bonding strength between the graphene-based coating and the functional conductive layer, a silane coupling agent can be sprayed on the interface between the two before coating. Specifically, the solution concentration of the silane coupling agent is 0.1% to 0.5%. After spraying evenly, it is naturally dried for 1 to 2 minutes to form a bonding promotion layer on the surface of the functional conductive layer.
[0034] In one possible implementation, the graphene-based coating needs to be cured by ultraviolet light curing technology. The wavelength of ultraviolet light is controlled at 350-380nm, and the curing time is 1.5-3 minutes. Under the action of ultraviolet light, the matrix (PEEK) of the graphene-based composite material can be quickly cross-linked to form a film, forming a close bond with the functional conductive coating; To further improve the mechanical properties and environmental stability of the coating, the coating can be heat treated after UV curing. Specifically, the coating is placed in a 120°C constant temperature oven for heat treatment for 30 minutes to make the coating structure denser and improve its anti-peeling performance; in some other embodiments, in order to optimize the conductivity of the coating, carbon nanotubes (CNTs) can also be added to the graphene-based coating liquid as a synergistic conductive material. The addition amount is 0.1% to 0.3%. The high aspect ratio of carbon nanotubes can further construct a three-dimensional conductive network, thereby reducing the overall resistance of the coating; The surface resistance of the graphene-based composite coating formed by the above method is generally controlled at 0.005 to 0.007 Ω / cm 2 The coating has no cracks or peeling after the thermal cycle test (15 to 25 cycles) at -40℃ to 80℃. At the same time, the coating has no obvious corrosion after the 1000-hour salt spray test in 5% sodium chloride solution, showing excellent corrosion resistance and environmental adaptability. This step is closely related to step S3. By forming a graphene-based composite coating with high conductivity and high chemical stability on the surface of the functional conductive layer, it not only optimizes the electron flow path, but also improves the reliability of the terminal in complex environments (such as high humidity, high temperature, etc.). The implementation of this step ensures the uniformity and adhesion of the graphene-based coating through the optimization of material formulation, the improvement of coating method and the application of UV curing technology.
[0035] S5. Performing subsequent curing treatment on the coated battery connector terminal to obtain a battery connector terminal with high corrosion resistance and excellent conductivity. The method can improve the power transmission stability of the terminal and extend its service life; In this embodiment, the specific implementation of the subsequent curing process includes the following contents: In some embodiments, the coated terminal is first cured by ultraviolet light, which can quickly cross-link the base material (such as polyetheretherketone) of the coating layer and promote the formation of a more stable intermolecular bond between the graphene particles and the base. As an option, the ultraviolet curing light source uses a UV lamp with a wavelength of 350 to 380 nm, and the curing time is controlled at 1.5 to 3 minutes. Under such conditions, the surface energy of the graphene-based coating is rapidly reduced, and the initial mechanical strength and conductive properties of the coating are significantly improved.
[0036] Specifically, during the UV curing process, the polymer chains in the polyetheretherketone matrix react with free radicals induced by UV light to form a cross-linked structure. This reaction can be described by the following chemical expression: PEEK-R·+PEEK-R·→PEEK-RR Among them, PEEK-R represents the active group of polyetheretherketone, and the free radicals form a more stable chemical structure through cross-linking; In some embodiments, in order to prevent cracking of the coating surface due to local overheating during UV curing, a low-speed fan may be used for cooling during the curing process. As a possible implementation method, the cooling wind speed is controlled at 0.5 to 1 m / s, which can reduce the local temperature rise without affecting the uniformity of the coating surface. After UV curing, in order to further improve the adhesion and overall performance of the coating, the coating is also heat treated in this embodiment. Generally, heat treatment can promote the formation of a tighter bond between the nanoparticles and eliminate the residual stress in the coating, thereby improving the mechanical strength and chemical stability of the coating. As an option, the temperature of the heat treatment is set to 120-150°C and the treatment time is 20-40 minutes; In one possible implementation, the heat treatment needs to be completed in a constant temperature box to ensure uniform temperature distribution. Specifically, a heat treatment box with a circulating fan can be used to evenly heat each area of the coating through circulating airflow. In addition, during the heat treatment process, a gradual heating method can be selected to avoid cracks in the coating due to thermal expansion caused by temperature differences. The heating rate is generally controlled at 1 to 3 °C / min; In some embodiments, in order to further optimize the corrosion resistance and electrical conductivity of the coating, external pressure may be applied to the coating during the heat treatment process to form a denser coating structure. Specifically, the coating may be placed in a low-pressure environment (the vacuum degree is controlled at 0.1-0.5 MPa) by a vacuum heat treatment device, and the microbubbles and pores inside the coating may be eliminated by external pressure, thereby improving the overall density of the coating. As a possible extension method, in order to ensure the interface bonding strength between the coating and the underlying conductive coating, the surface tension of the coating can be tested before heat treatment. The detection method can use a contact angle tester to measure the contact angle of the coating surface. The contact angle is generally controlled below 40° to ensure that the wettability of the coating reaches the optimal state; In some other embodiments, in order to verify the curing effect of the coating, the performance of the coating after the heat treatment is completed can be tested. For example, the density of the coating surface can be observed by scanning electron microscopy (SEM), or the surface resistance of the coating can be measured by a resistance tester. In general, the surface resistance of the coating should be controlled at 0.005 to 0.007 Ω / cm 2 The coating surface should be within the specified range and there should be no obvious cracks or pores; After the heat treatment is completed, in order to avoid deformation or cracking of the coating during rapid cooling, a slow cooling method can be selected. Specifically, the treated terminals are placed in a slow cooling box at 70-90°C and naturally cooled to room temperature. This method can effectively reduce the accumulation of thermal stress in the coating and further improve the stability of the coating; Through the above-mentioned subsequent curing treatment, the obtained battery connector terminals show excellent corrosion resistance and electrical conductivity. Specifically, after the thermal cycle test at -40℃~80℃ (15~25 cycles), the coating remains intact and crack-free; at the same time, after 1000 hours of salt spray test in 5% sodium chloride solution, the coating has no obvious corrosion. Combined with the test results of the physical and chemical properties of the coating, this step ultimately achieves high density and high stability of the coating, providing technical guarantee for the long-term use of the battery connector terminals; This step, as the last link of the entire process, is closely connected with the previous steps (especially the graphene-based composite material coating process). Through reasonable curing treatment, a stable bond is formed between the coatings, and the density, adhesion and chemical stability of the coating are further optimized, while ensuring the integrity of the conductive network and the environmental adaptability of the coating. The curing treatment is carried out in two steps: UV curing and heat treatment to fully meet the use requirements of battery connector terminals in complex environments.
[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A battery connector terminal electroplating method, characterized in that: The following steps are involved: Pre-treat the battery connector terminal surface to remove impurities and oxides; Use nano-metal electroplating solution to electroplate the bottom coating of the battery connector terminal to form a dense metal protective film; depositing a functional conductive coating on the base coating to optimize electron flow paths; Applying graphene-based composite coatings on functional conductive coatings to enhance conductivity and corrosion resistance; The coated battery connector terminal is subsequently cured to obtain a battery connector terminal with high corrosion resistance and excellent conductivity. The method can improve the power transmission stability of the terminal and extend its service life.
2. A battery connector terminal electroplating method according to claim 1, characterized in that: The pre-processing step comprises: Immerse the battery connector terminals in 2% to 5% by mass alkaline cleaning solution and perform ultrasonic cleaning at 35°C to 50°C; Immerse the cleaned battery connector terminals in a 3% to 7% hydrochloric acid solution for pickling and activation for 2 to 5 minutes; After rinsing with deionized water, the battery connector terminals are dried at 75 to 90° C. for 3 to 7 minutes.
3. A battery connector terminal electroplating method according to claim 1, characterized in that: The nano metal electroplating solution is a copper-nickel alloy electroplating solution, the concentration of copper ions is 30-40 g / L, the concentration of nickel ions is 10-20 g / L, and 2-5 g / L of potassium sodium tartrate as a complexing agent and 4-6 g / L of sodium citrate as a dispersant are added during the electroplating process.
4. A battery connector terminal electroplating method according to claim 1, characterized in that: The bottom coating electroplating adopts a pulse electroplating mode with a pulse period of 8 to 12 ms, a duty cycle of 40% to 60%, a current density of 1.5 to 3 A / dm², an electroplating temperature of 40 to 50°C, and an electroplating time of 25 to 35 minutes. During the electroplating process, ultrasonic assistance with a frequency of 35 to 45 kHz and a power of 250 to 350 W is applied.
5. A battery connector terminal electroplating method according to claim 1, characterized in that: The functional conductive coating is composed of a nickel-based material doped with silver nanoparticles, the average size of the silver nanoparticles is 5 to 10 nm, the mass ratio accounts for 0.5% to 1.5% of the total weight of the functional coating, and the nickel ion concentration is 15 to 25 g / L.
6. A battery connector terminal electroplating method according to claim 5, characterized in that: The functional conductive coating is deposited in a direct current electroplating mode with a current density of 0.8 to 1.5 A / dm², an electroplating temperature of 45 to 55° C., an electroplating time of 12 to 20 minutes, and a magnetic stirrer is used to stir the electroplating solution at a speed of 80 to 120 rpm during the electroplating process.
7. A battery connector terminal electroplating method according to claim 1, characterized in that: The main components of the graphene-based composite material coating are graphene and polyetheretherketone, the mass ratio of the graphene is 2% to 4%, the mass ratio of the polyetheretherketone is 95% to 97%, and the graphene is uniformly distributed in the polyetheretherketone by a high-speed shear dispersion method.
8. A battery connector terminal electroplating method according to claim 7, characterized in that: The graphene-based composite material is coated by spin coating, with a coating thickness of 10 to 20 μm. After coating, ultraviolet light with a wavelength of 350 to 380 nm is used for curing, and the curing time is 1.5 to 3 minutes.
9. A battery connector terminal electroplating method according to claim 1, characterized in that: The bonding force between the functional conductive coating and the graphene-based composite material coating is enhanced by spraying a silane coupling agent, and the concentration of the silane coupling agent solution is 0.1% to 0.5%.
10. A battery connector terminal electroplating method according to claim 1, characterized in that: The surface resistance change rate of the obtained battery connector terminal is less than 5% in the temperature range of -40 to 80°C, and its corrosion resistance is shown in the salt spray test as a corrosion resistance time of 1000 to 1500 hours in a 5% sodium chloride solution.
Citation Information
Cited By
Improved photoelectric coupler packaging electroplating process
CN120119248A
High-durability environment-friendly earphone charging terminal and electroplating method thereof
CN120485895A
Vacuum deposition method for gradient composite coating of contact terminal
CN121250356A